Direct Current Characteristics of AlGaN/GaN High-Electron-Mobility Transistors with Different Channel Widths. (1st January 2019) - Lin, Wei-Chun; Zhong, Yi-Nan; Tsai, Ming-Yan; Ho, Wei-Cheng; Yu, Yi-Hsuan; Hsin, Yue-Ming
Abstract : AlGaN/GaN high-electron-mobility transistors with different channel configurations were fabricated and characterized. Channel configuration was designed to have the source, gate, and drain metal contacts of the same size but with different channel widths, which was achieved by the current blocking region. Current density, subthreshold swing, and transconductance (gm ) improved with the decreasing channel width. A significant improvement was observed in gm because of a large gate width (WG ) to channel width (Wchannel ) ratio. A device with a WG /Wchannel of 4 has a gm of 239 mS/mm, whereas a device with a WG /Wchannel of 1 has a gm of 127 mS/mm.